(untitled) (Comparative Professional Pedagogy, 2022)
The article substantiates the peculiarities in the development of pedagogical education in Sweden in early 21st century. It is defined that the professional training of teachers in Sweden is carried out in the system of higher education and is practically implemented in the structure, goals and content of professional education programs. The main principles of teacher training system in Sweden, namely democracy, openness, continuity and integrity, flexibility, continuity, innovation, differentiation, coordination of interests in the group and teamwork are characterized. It is highlighted that pedagogical education in Sweden is aimed at practice-oriented professional activity, at teachers’ training based on competence-oriented and person-oriented approaches. It is emphasized that the system of modern pedagogical education in Sweden is quite flexible and meets the needs of society in the number and qualifications of teachers who have the opportunity to adjust their pedagogical profile throughout their life. The system of in-service training of teachers in Sweden, which is based on an approved curriculum, continuous self-development, innovative forms and methods of work, which determine the priorities of the professional development of teachers, is characterized. Special attention is paid to the formation of democratic values in education, which contribute to the development of civil society, education of active citizens who know and are able to exercise their rights, participate in democratic processes and make responsible decisions. It is concluded that in Sweden, like in other Scandinavian countries, there is a tendency to individualize the educational process, and the interdisciplinary, integrated nature of education becomes the new benchmark of a democratic society that creates conditions for the formation of a new view on freedom of creativity and the realization of teacher professionalism.